Performance of Orthogonal Frequency Division Multiplexing Based Advanced Encryption Standard - Truong, Duc-Tai; Nguyen, Quoc-Tuan; Dinh, Thai-Mai Thi (VNU Journal of Science: Computer Science and Communication Engineering, 2020)
Currently, there are a lot of secure communication schemes have been proposed to hide secret contents. In this work, one of the methods deploying encryption to cipher data is represented. The primary object of this project is applying Advanced Encryption Standard (AES) in communications based Orthogonal Frequency Division Multiplexing (OFDM). This article discusses  the security of the method encrypting directly QAM symbols instead of input bit-stream. This leads to improving the security of transmitting data by utilization of authentication key between the mobile and base station. The archived results demonstrate that the performance of the AES-OFDM system is completely acceptable to compare with the criteria for 4G. Keywords: Orthogonal Frequency Division Multiplexing (OFDM), Advanced Encryption Standard (AES), Quadrature Amplitude Modulation (QAM), Authentication Key, Cellular Network, Encryption, Physical Layer, 4G, LTE. References [1] M.A. Jessen, “Wireless communication security: Physical-Layer techniques exploiting radio and propagation characteristics”, Wireless Information Technology and Systems (ICWITS), IEEE International Conference, 2012.[2] M. Kim, M. Lee, S. Kim, D. Won, “Weakness and Improvements of a One-time Password Authentication Scheme”, International Journal of Future Generation Communication and Networking, 2009. [3] Alabaichi, Ashwaq, Salih, Adnan, “Enhance security of advance encryption standard algorithm based on key-dependent S-box”, 2015, pp. 44-53. [4] S. Xiao, W. Gong, D. Towsley, “Secure Wireless Communication with Dynamic secrets”, IEEE INFOCOM, 2010.[5] N.U. Rehman, L. Zhang, M.Z. Hammad, “ICI cancellation in OFDM system by frequency offset reduction”, Journal of Information Engineering and Applications, 2014. [6] Nikita Agrawal, Neelesh Gupta, “Security of OFDM through Steganography”, International Journal of Computer Applications 121(20) (2015) 41-43. [7] A. Al-Dweik, M. Mirahmadi, A. Sharmi, Z. Ding, R. Hamila, “Joint Secured and Robust technique for OFDM systems”, Western University, Canada, IEEE ICC 2013. [8] G.R. Tsouri, D. Wulich, “Securing OFDM over Wireless Time-varying channel using subcarrier overloading with Joint signal constellations”, Hindawi Publishing Corporation, EURASIP Journal on Wireless Communication and Networking, 2009. [9] D. Rajaveerappa, A. Almarimi, A., “RSA/Shift secured IFFT/FFT based OFDM wireless system,” Fifth International Conference on Information Assurance and Security, 2009. [10] M. Hilmey, S. Elhalafwy, M. Zein Eldin, “Efficient transmission of chaotic and AES encrypted images with OFDM over an AWGN channel”, 2009 International Conference on Computer Engineering & Systems, Cairo, 2009, pp. 353-358. [11] B.V. Naik, N.L.K. Sai, C.M. Kumar, “Efficient transmission of encrypted images with OFDM system”, 2017 IEEE International Conference on Power, Control, Signals and Instrumentation Engineering (ICPCSI), Chennai, 2017, pp. 2383-2388. [12] S.M.S. Eldin, “Optimized OFDM Transmission of Encrypted Image Over Fading Channel”, An International Journal on Sensing and Imaging 15(1) (2014), pp. 1-14. [13] C. Akbar, H. Mahmood, Q. Minhas, I. Mustafa, “Secure AES OFDM with channel reciprocity exploitation through relative calibration”, 2016 International Conference on Open Source Systems & Technologies (ICOSST), Lahore, 2016, pp. 54-61. [14] Y. Liang, J. Ren, T. Li, “Secure OFDM System Design and Capacity Analysis Under Disguised Jamming”, in IEEE Transactions on Information Forensics and Security 15 (2020) 738-752. [15] Westlund, B. Harold, “ NIST reports measurable success of Advanced Encryption Standard ”,Journal of Research of the National Institute of Standards and Technology, 2002. [16] B. Schneier, J. Kelsey, D. Whiting, D. Wagner, C. Hall, N. Ferguson, Performance Comparison of the AES Submissions, Proceedings of the Second AES Candidate Conference, 1999. [17] S. He, A. Tang, H. Zhang, “A high-performance Implementation of OFDM-MIMO base-band in wireless video system”, Information Technology Journal 13 (2014), pp. 1678-1685.